RISKS OF THE FUNCTIONING OF THE ECONOMIC SECURITY SYSTEM OF AN ENTERPRISE IN WAR TIME - LUHOVA, Viktoriia; DEMCHENKO, Kateryna; IVANCHENKOVA, Larysa; TKACHUK, Oleksandr; LAGODIIENKO, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article presents a comprehensive analysis of the risks affecting the functioning of the economic security systems of Ukrainian enterprises under martial law. It examines the transformation of the country’s economic environment caused by the full-scale war, leading to profound structural shifts across the financial, labor, logistics, and production spheres of business activity. It is substantiated that economic security in wartime takes on a new conceptual meaning, encompassing not only financial stability but also the enterprise’s ability to maintain viability, adaptability, and recoverability in an environment marked by high uncertainty and destructive external influences. Based on an analysis of scholarly sources, official statistics, reports of international institutions, and empirical evidence from Ukrainian companies, the study systematizes the key wartime risks: operational, financial, informational-communication, legal, and strategic-reputational. Operational risks arise from infrastructure destruction, supply chain disruptions, production relocation, and shortages of skilled labor. Economic risks include rapid increases in operating costs, declining revenues, inflationary pressures, exchange rate volatility, and limited access to credit and investment resources. Information-related threats encompass cyberattacks, data leaks, and communication system failures, which hinder effective interaction between enterprises and their partners or clients. Legal risks include frequent regulatory changes, uncertainty in legal enforcement, and the potential requisition or loss of assets. Strategic risks manifest in reduced investment attractiveness, loss of market positions, and the inability to implement long-term development projects. The article proposes a systematization of risks and substantiates the need for an adaptive, proactive model of economic security management that ensures resilience and operational continuity, laying the foundation for post-war recovery and enterprise modernization. The practical significance of the research lies in the applicability of the proposed approaches to improve risk management strategies, enhance monitoring systems, and strengthen the economic resilience of Ukrainian enterprises.